Understanding the social impacts of enforcement activities on illegal wildlife trade in China - Sifan Hu; Yu Cheng; Rong Pan; Fasheng Zou; Tien Ming Lee (Ambio, 2022)
Illegal wildlife trade enforcement is a cornerstone conservation strategy worldwide, yet we have a limited understanding on its social impacts. Using Chinese online wildlife seizure news (2003–2018), we evaluated the interactions among enforcement operations, news frequency, and social engagement (i.e., whistle-blowing) frequency. Our results showed that intensive enforcement operations, which commenced after 2012, have social impacts by increasing the frequency of all seizure news significantly by 28% [95% Confidence Interval (CI): 5%, 51%] and those via whistle-blowing by 24% [95% CI: 2%, 45%], when compared to counterfactual models where possible confounding factors were accounted for. Furthermore, we revealed the potential interaction between enforcement seizure news with and without social engagement, and the consequential social feedback process. Of the species identified from ‘whistle-blowing’ news, up to 28% are considered as high conservation priorities. Overall, we expanded our understanding of the enforcement impacts to social dimensions, which could contribute to improving the cost-effectiveness of such conservation efforts.